Circulations transnationales en matière d'éducation (XIXe-XXe siècles) : note de synthèse des travaux d'un champ de recherche en expansion - Sébastien-Akira Alix; Pierre Kahn (Nantes Université, 2023)
Since the last quarter of the 20th century, many researchers and historians have endeavored to trace the emer-gence, development, and establishment of a site of circulation - involving actors, objects, knowledge, networks, etc. - between different regions of the world. This historical scholarship has been central to the emergence of what is now commonly known as the transnational turn in the humanities and social sciences. In the field of the history of education, this transnational perspective has grown quite significantly in France in recent years. Without claiming to be exhaustive, this article aims at highlighting the interest and stakes of this scholarly approach that has signifi-cantly contributed to our understanding of educational realities in the 19th- and 20th-centuries, especially in tran-satlantic areas.